The Value of Methodological Pluralism in the Study of Locke on Slavery and Absolutism: A Rejoinder to Felix Waldmann - Olsthoorn, Johan; Van Apeldoorn, Laurens (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2021)
In a critical note published in Locke Studies, Waldmann challenges our recent reconstruction of Locke’s thesis, developed across the Second Treatise of Government, that humans cannot possibly agree to subject themselves to absolute rule. Call this thesis No Contractual Absolutism. Our reconstruction, Waldmann objects, “neglects a basic datum of scholarship”: i.e., that Locke’s Second Treatise intended to counter Filmer’s political theory. Our reply is two-pronged. First, we argue that No Contractual Absolutism cannot plausibly be construed as an attack on Filmer, since it challenges a thesis that he did not hold. Indeed, as for him no form of government can be contractual in origin, Filmer would have agreed with Locke that absolute rule cannot be instituted by agreement. As our initial article suggested, the standard view about whom the polemical target is of the Second Treatise requires qualification with respect to No Contractual Absolutism. Second, we contend that Waldmann’s concerns rest on discipline-specific methodological assumptions, which are unhelpful for the kind of analytical reconstruction we advanced. We conclude with a plea for methodological pluralism in the study of Locke’s thought.